Historical dictionary of international intelligence - West, Nigel (Historical dictionaries of intelligence and counterintelligence., 2015)
This second edition of Historical Dictionary of International Intelligence covers its history through entries on espionage techniques, categories of agents, crucial operations spies, defectors, moles, double and triple agents, and the tradecraft they apply.